WSTĘP. AKTYWNOŚĆ, PODMIOTOWOŚĆ, TOŻSAMOŚĆ – OSOBY Z NIEPEŁNOSPRAWNOŚCIAMI W SPOŁECZNYCH PRZESTRZENIACH ŻYCIA CODZIENNEGO - Jakub Niedbalski; Mariola Racław (Studia Humanistyczne AGH, 2020)
This introduction is intended to outline the topics of a special issue on the notions of activity, subjectivity and identity of people with disabilities. The matters concerning disability, both in the scientific discourse and social perception, are constantly under discussion and broad analysis, thus the different perspectives and ways of addressing them. While crucial but also somewhat opposite to each other are the medical and social models of disability. There is a biopsychological model in between them, which assigns an individual with an active subject role having some characteristics of biological and psychological nature, as well as those related to the social functioning of that individual. A key to this approach is an action called empowerment, meaning the process of regaining an individual’s self-confidence and self-awareness. Identity grows here on awareness of one’s own physicality and mental potential, and it is related to the notion of subjectivity, which is expressed by freedom and functioning autonomy of persons with disabilities in various life spheres. This includes the possibilities to play different social roles related to cultural patterns and their implementation, e.g. a student, a worker, a parent, a spouse, etc. Therefore, the issue incorporates theoretical and empirical texts on the matters of subjectivity and identity of persons with disability, referring to, among other things, such activities as education, work, or participation in the broadly understood culture.